The role of radiotherapy in the treatment of brain metastases - Niwińska, Anna; Pogoda, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2009)
Life extension in cancer patients and wide availability of neuroimaging modalities of the brain led to increase of the brain metastases detection. The most common sources of brain metastases are lung cancer (50%), breast cancer (15-20%), melanoma (10-15%), colon cancer and renal cancer; although in 10-15% of patients the primary site is unknown. The prognosis in patients with brain metastases depends on performance status, neurological symptoms, age, number of tumors in the brain, status of the primary tumor and extracranial metastases. Optimal local and systemic treatment have additional impact on prognosis. Currently suboptimal treatment of brain metastasis is observed. This approach deprives some patients longer survival. RPA RTOG classification is the most useful method of selection of patients for optimal treatment. In the present review, whole brain radiotherapy, stereotactic radiosurgery and prophylactic cranial irradiation are presented. The indica-tions and the efficacies of these treat-ment methods are discussed.